Analisis Keterkaitan Konsep Dasar Geografi dengan Materi IPS di Kelas VI Sekolah Dasar - Niwi Sruti Handayani (Pena Edukasia, 2024)
The importance of integrating the basic concepts of geography into the teaching of Social Studies in elementary schools, especially in grade six, cannot be overstated. The problems addressed by this research include the absence of concrete examples connecting the basic concepts of geography with Social Studies materials, the inadequate development of teaching materials that integrate geography concepts, and the low ability of students to analyze human relationships with their geographical environment. The research objectives were to identify the relationship between the basic concepts of geography and Social Studies materials, design effective teaching strategies to integrate these concepts, and develop teaching materials to support integrated learning. The methodology involved a literature review based on relevant qualitative research. The results highlighted the basic concepts of geography and their relevance to Social Studies. Strategies for effective integration include identifying relevant concepts, contextual planning, and varied teaching methods. The implications of this study indicate that integrating the basic concepts of geography into Social Studies in grade six can enhance students' understanding of their environment, improve critical and spatial thinking skills, and help them analyze social problems contextually. By utilizing geography-based learning resources and training teachers, the aim is to make Social Studies learning more meaningful, contextual, and relevant to students' real lives through the optimal integration of geographic concepts. This research contributes new ideas for the development of Social Studies learning that is more interesting and integrated with geography concepts in elementary schools.